Factors influencing bladder management in male patients with spinal cord injury: a qualitative study - Julia, P.E.; Ng, C.J.; Low, W.Y. (2014)
Study design: Qualitative study using individual in-depth interviews. Objectives: The objective of this study was to explore the factors influencing the choice of bladder management for male patients with spinal cord injury (SCI). Setting: Public hospitals in Malaysia. Methods: Semistructured (one-on-one) interviews of 17 patients with SCI; 7 were in-patients with a recent injury and 10 lived in the community. All had a neurogenic bladder and were on various methods of bladder drainage. Interviews were audio-recorded, transcribed verbatim and analyzed using thematic analyses. Results: The choice of bladder management was influenced by treatment attributes, patients' physical and psychological attributes, health practitioners' influences and social attributes. Participants were more likely to choose a treatment option that was perceived to be convenient to execute and helped maintain continence. The influence of potential treatment complications on decision making was more variable. Health professionals' and peers' opinions on treatment options had a significant influence on participants' decision. In addition, patients' choices depended on their physical ability to carry out the task, the level of family support received and the anticipated level of social activities. Psychological factors such as embarrassment with using urine bags, confidence in self-catheterization and satisfaction with the current method also influenced the choice of bladder management method. Conclusion: The choice of bladder management in people with SCI is influenced by a variety of factors and must be individualized. Health professionals should consider these factors when supporting patients in making decisions about their treatment options.